Education Funding Management as an Effort to Improve the Quality of Education in Islamic Boarding Schools - Zakiya, Nabila; Hidayatullah, Nurfitri; Oktaviani, Oktaviani; Yahya, Yahya (International Journal of Educational Dynamics, 2023)
Education funding is a cost that must be spent, namely the budget or details of costs incurred to fund all Islamic boarding schools activities related to education. In the execution of education, funding is needed with an accurate budget so that it is in accordance with the required reputation. Regarding the direction of the research conducted, the researcher is intended to describe education funding management as an effort to adjust the quality of education in Islamic boarding schools. This study uses qualitative research with identifiyinganalysis techniques, namely library research or commonly called article studies. Article or article study can be interpreted as a series of activities related to methods of collecting library data, reading and recording and processing research materials. The conclusion from the research conducted by the author is that the application of the education rule as well as possible cannot be separated from a good management system, with the arrangement of education funding that is right on target, it will determine the level of effectiveness and success of educational goals.